The Role of Human Resources Development (HRD) in Increasing the Competitive Advantage of Brownies Cinta Employees (PT Berkah Ridho Cinta Indonesia) - Zidan Himmatul Ama; Daryono Soebagiyo; Nur Andriyani (Income Journal Of Economics Development, 2024)
The rapid changes in the global business environment and intense competition drive companies to enhance competitive advantage through effective human resource management. This research elucidates the strategic role of Human Resource Development (HRD) in improving the competitive advantage of employees at PT Ridho Berkah Cinta Indonesia, known as Brownies Cinta. This qualitative study adopts a triangulation approach through in-depth interviews with HRD to understand the role of HRD in recruitment, training, performance management, and employee skill development. The research findings indicate that HRD plays a crucial role in designing HR strategies, encompassing the enhancement of religious knowledge, general knowledge, and skills among employees. Nevertheless, there is potential to improve the digital ecosystem as a step towards competitive advantage in the digital era. The research's conclusion emphasizes the urgency of HRD's role in creating an innovative and responsive organizational culture, highlighting the need for digital strategy integration to meet employee needs and face future challenges.